Development of Leclanche cell for microsystem applications - Nor Liza Mohd Zawi (Kulliyyah of Engineering, International Islamic University Malaysia, 2014)
The efficacy of MCM-41inorganic membrane as a separator material for Zn/MnO2 Leclanche cell is studied.The study preceded with stability test of MCM-41 material in the acidic medium of ammonium chloride (NH4Cl) i.e. the electrolyte of Leclanche cell. The X-ray diffraction profiles and FESEM observations substantiated the stability of hexagonally ordered nanostructure of MCM-41 under such environment and support its use as membrane separator in Zn/MnO2 Leclanche cell. The viability of MCM-41 membrane separator in Zn/MnO2 Leclanché cell is studied using two types of cell design i.e. the round button cell R2025 and the PCB-embedded microbattery. For the R2025 cell design, MCM-41 membrane was dip coated onto zinc electrode from sol gel parent solution comprising of tetraethiylortosilicate (TEOS) as the silica construction material and cethyltrimethylammonium bromide (CTAB) cationic surfactant as the organic template for mesoporous structure. The cathodic paste mixture comprised of carbon black, polyethylene glycol (PEG), manganese dioxide and ammonium chloride. In formulating the cathode mixture, it was observed that the carbon black content and „dryness‟ of the paste were the most important component/factor that affected up to 80 % of the cell performance. On the other hand the use of electrolytic MnO2 (EMD) instead of pure MnO2 would be more beneficial at high current drain. MCM-41 material was discovered to be beneficial as the cathodic additive. It is conjectured that the network of nanochannels of MCM-41 provided accessible ionic pathways penetrating the insulating layer of discharge products of MnO2 thus contributing to better cathodic efficiency. Besides, the hydrophilic porous structure and high surface area of MCM-41 are advantageous as electrolyte reservoir in the cathodic mixture. In enhancing the anodic efficiency, the use of the electrodeposited zinc anode increased the storage capacity by 37 % and extended the peak power by 46 %. Taking advantage of the dip coating method in preparing the MCM-41 membrane, the Zn/MnO2 Leclanché cell was constructed in the bipolar cell configuration. Merely by changing the cell design, the capacity improvement was most notable. The total cell energy output was extended by 69%, from 10.7 mWh to 18.1 mWh, rated at 500 A. The peak power output was increased by an order of magnitude from 700 μW at load current of 1400 μA to 1330 μW at 2400 μA. A novel, low cost Zn/MnO2 Leclanché cell of compact, micron-scale thickness is designed and constructed. The cell design template was developed on FR- 4 printed circuit board (PCB) utilizing PCB processing techniques. The cell design template developed can easily be extended to multi cell configuration as demonstrated for the twin cell design in this work. The use of dry cathode paste formulation, electrodeposited zinc anode and spin coated MCM-41 membrane separator, allowed the cell to be constructed to sufficiently thin with ease. Measuring 10 mm in diameter and 365 m thick, the Zn/MnO2 Leclanché microcell was capable to produce an output of 109 Wh when rated at 100 A. Finally the fabricated Zn/MnO2 Leclanché microbatteries were tested as power sources to operate the National Semiconductor LM94021 multi-gain analogue temperature sensor and Honeywell HIH-5030 humidity sensor. The microbatteries were capable to power both sensors for a considerable period of time i.e. 14 hours and 28 hours respectively.